Corporate Culture, Leadership Style, and Performance of Foreign and Local Organizations in Malaysia - Jaharuddin, Nor Siah (2003)
This study examined the relationship between corporate culture, leadership style, and performance in Malaysia. This research also investigated the corporate culture and leadership style in local and foreign organizations. Organizational culture was measured by using the Competing Values Framework (Quinn and Rohrbaugh, 1983; Cameron and Quinn, 1999), leadership style was measured by using the model developed by Javidan & Dastmalchian {1993} and Dastmalchian (2000), while performance was measured in terms of profitability. A total of 1 34 companies, comprising of 60 foreign companies and 74 local companies participated in the study. The Chi-square tests, Pearson correlation, and cross tabulation tests analysis were carried out to measure the significant association between the variables. The findings showed that local companies tend to have a hierarchical culture, while foreign companies tend to have a clan and result-oriented culture. As for the leadership style, the results showed the similarity of both local and foreign companies in practicing an auditor style of leadership. Cross-tabulation results also revealed that there is an association between organizational culture and leadership style in foreign organizations but no association was found in local organizations. With regards to the relationship between organizational culture and performance, it was found that there is no association between them in foreign or local companies due to other influencing external factors. In addition, no significant relationship was found between leadership style and performance in foreign or local companies.